Health Educations about Steps for early Breastfeeding on Successful Breastfeeding in Post-Partum Mothers in the Kampak Health Center Area, Trenggalek Regency - Hikmatul Zulva (Master of Public Health Program Universitas STRADA Indonesia, 2024)
The ineffective implementation of health promotion programs is one of the factors influencing exclusive breastfeeding coverage. The behavior of giving exclusive breast milk will emerge after there is socialization about the importance of giving exclusive breast milk to pregnant and breastfeeding mothers. The aim of the research is to determine the effect of health education regarding early breastfeeding steps on the success of breastfeeding in post-partum mothers in the Kampak Community Health Center area, Trenggalek Regency. Research designs is quasi – experimental with a plan one group pretest-posttest. The research population was all post-partum mothers in the Kampak Trenggalek Community Health Center area, an average of 35 people per month. Using sampling technique accidental sampling with a sample of 31 people. Independent variable is health education regarding initial breastfeeding steps, dependent variable is breastfeeding success in post-partum mothers. Data was taken using an observation sheet instrument and analyzed using statistical tests Wilcoxon signed rank. The results of the research were obtained before health education was carried out regarding the steps for initial breastfeeding, all respondents were unsuccessful in breastfeeding, as many as 31 respondents (100%) while after health education was carried out regarding the steps for initial breastfeeding, the majority of respondents were successful in breastfeeding, as many as 22 respondents (71%) . There is an influence of health education about the steps for early breastfeeding on the success of breastfeeding in post-partum mothers in the Kampak Community Health Center area, Trenggalek Regency, where the results of statistical tests Wilcoxon signed ranks test obtained p value 0.000 < 0.05. Health education can increase breastfeeding success, so that health education influences breastfeeding success. Providing health education about early breastfeeding will help post-partum mothers to breastfeed properly so that breastfeeding success will be achieved.